Hormone therapy: more risks than benefits or more benefits than risks? - Danckers, Luis (2015)
Menopause is the clinical manifestation of ovarian function cessation that is associated with symptoms that deteriorate quality of life and increases chronic diseases risk, affecting woman’s health in her last third of her life. It seemed hormonal replacement therapy (HT) was the solution to counteract women’s climacteric effects and keep women ‘young forever’. Women’s Health Initiative (WHI) study publication showed negative effects of a particular HT in older women. This paper reviews HT impact, evaluating benefits against risks and trying to establish when clinical therapy is justified in climacteric women.